Experimental investigation on ignition and combustion characteristics of n-butane/air mixtures by glow plug in miniature chamber. (15th August 2020) - Zhou, Guangzhao; Jiang, Liqiao; Gu, Cheng; Wang, Xiaohan; Yang, Weibin; Zhao, Daiqing
Abstract: The aim of this work is to understand the ignition and combustion behaviors of n -butane/air mixtures under glow plug ignition in the start-up condition of miniature IC engines. We utilized a centimeter-scale constant-volume chamber setup to investigate the effects of glow plug heating power, equivalence ratio, and initial pressure on the characteristics of ignition and flame propagation of n -butane/air mixtures. Results indicated that the ignition time and ignition temperature decrease as the heating power increases and the flame propagation time is weakly sensitive to that. Increasing the initial pressure can reduce the ignition time, decrease the ignition temperature and slow flame propagation; except for the flammable limit, the ignition time and ignition temperature increase as the equivalence ratio increases, in addition, the flame propagation is fastest at φ  = 1.2. Furthermore, an obvious two-stage combustion phenomenon was observed under fuel-rich flame propagation conditions. Overall, the order of influencing factors on the ignition characteristics shows heating power > initial pressure > equivalence ratio, and that on the flame propagation characteristics shows equivalence ratio > initial pressure > heating power in present experimental conditions.